CULTURAL HERITAGE PRODUCT MARKETING AND HOSPITALITY BUSINESS PERFORMANCE: AN EMPIRICAL ASSESSMENT OF OSUN-OSOGBO FESTIVAL, OSUN STATE - Joseph Sunday Etuk; Victoria Kareem Idowu (Scholar Express Journal, 2025)
Although Nigeria is blessed with rich cultural heritage, the level of tourism performance in Nigeria is unfortunately very low as manifested through low tourist arrivals and low spending with little contribution to the Gross Domestic Product. The purpose of the study was to determine the link between cultural heritage (Osun-Osogbo cultural festival) marketing and hospitality business performance in Osogbo, Osun State, drawing our empirical analysis from the just concluded Osun-Osogbo cultural festival in August, 2024. The study adopted the survey method of the quasi-experimental design. The population used for the study consisted of 150 officials drawn from 10 hotels and 5 restaurants within Osogbo using the purposive sampling method and the questionnaire as the instrument for data collection. Both descriptive and inferential statistical analytical tools were employed. The analysed data revealed that heritage product preservation, promotion and celebration were important in marketing the Osun-Osogbo cultural festival to domestic and international tourists. The study further revealed that hotels and restaurants operating around the Osun-Osogbo grove recorded an increase in customers’ patronage and revenue during the festival. However, the level of patronage and revenue recorded by hotels and restaurants during the year’s festival in 2024 was low compared to their performance at the same period in 2023. It was concluded that the way the Osun-Osogbo cultural festival has been marketed through heritage preservation, promotion and event celebration influenced to a large extent, hospitality business performance. The study recommended collaborative and extensive advertising, security management and involvement of the Nigerian Tourism Development Corporation (NTDC) and private sector in the marketing of the festival in the future
Keywords: Cultural heritage marketing; Osun-Osogbo cultural festival